Phylogenetic Analysis and Certain Risk Factors of Chlamydia Abortus in Ewes in Nineveh Governorate, Iraq - Yarub Abulkhaliq Rhawy; Osamah Al-Iraqi. (مجلة الانبار للعلوم البيطرية, 2024)
Chlamydia is an obligate intracellular Gram-negative organism that causes abortion, or "enzootic abortion of ewes", which is characterized by causing economic loss in sheep breeding. Chlamydia abortus spread could be stopped, and monitoring efforts could be more successful by gathering data on the condition of the disease. This ground-breaking study focused on the phylogenetic analysis and certain risk factors of Chlamydia abortus in ewes in Nineveh governorate, Iraq. 52 placenta samples were collected, representing 52 flocks (8660 ewes) who suffered from abortion in various Nineveh provincial locations between August 2022 and January 2023. Two local sequences were submitted to GenBank and assigned the accession numbers OR334580 and OR334581. The Chlamydia abortus 16S rRNA sequences were analyzed using the GenomeNet multiple sequence alignment tool (CLUSTALW), an online resource. After that, the sequences were compared to other Chlamydia abortus sequences that were accessible in the GenBank using NCBI BLAST (BLASTn) of NCBI. The Tamura-Nei model in the MEGA11 software program was used to create the phylogenetic trees. Results indicate that 15.38% (8/52) of the ewes had positive results for Chlamydia abortus, which was significantly affected by the increase in herd size and interspecies farming. Two sequences were put through individual sequence analysis, which revealed new Chlamydia abortus sequences, which were recorded for the first time in the governorate of Nineveh. We concluded that a higher risk of infection occurs in farms that contain more than 100 ewes and are mixed with other species of animals.